Orientasi Kebijakan Reformasi dalam Rangka Menentukan Sikap Kepemimpinan Bangsa Pasca Pemilu 2004 - Shaleh, Chairul (Unisia, 2016)
One of the problem according to perspective of civility humanity is May, 1998 tragedy that denotes the beginning of reformation in Indonesia. Many reformation reformula tions that all of aspect that start to conduct. Actually, one of reformation goal is reforming sustainable development. According to the author of this article, the policy of reformation of development including to overcome the crisis of economics that becoming a short run policy and the realization of rteformation it self that constitutes a long run policy. Actually Indonesian needs a national leader (a president or a vice president) who has acceptability, capability and competency.